The developments of cyan emitting phosphors to fulfill the cyan emission gap of white-LEDs - Khan, Noor Zamin; Khan, Sayed Ali; Chen, Weilong; Padhiar, Muhammad Amin; Abbas, Muhammad Tahir; Ullah, Zakir; Runowski, Marcin; Xu, Xin; Zheng, Ren-Kui (Frontiers in Chemistry, 2023)
Future generations of solid-state lighting (SSL) will prioritize the development of innovative luminescent materials with superior characteristics. The phosphors converted into white light-emitting diodes (white LEDs) often have a blue-green cavity. Cyan-emitting phosphor fills the spectral gap and produces “full-visible-spectrum lighting.” Full-visible spectrum lighting is beneficial for several purposes, such as light therapy, plant growth, and promoting an active and healthy lifestyle. The design of cyan garnet-type phosphors, like Ca2LuHf2Al3O12 (CLHAO), has recently been the subject of interest. This review study reports a useful cyan-emitting phosphor based on CLHAO composition with a garnet structure to have a cyan-to-green emitting color with good energy transfer. It could be employed as cyan filler in warm-white LED manufacturing. Due to its stability, ability to dope with various ions suitable for their desired qualities, and ease of synthesis, this garnet-like compound is a great host material for rare-earth ions. The development of CLHAO cyan-emitting phosphors has exceptionally high luminescence, resulting in high CRI and warm-white LEDs, making them a viable desire for LED manufacturing. The development of CLHAO cyan-emitting phosphors with diverse synthesis techniques, along with their properties and applications in white LEDs, are extensively covered in this review paper.